Supervisor control strategy of synchronizer for wet DCT based on online estimation of clutch drag torque. (January 2016) - Lu, Tongli; Li, Hongkui; Zhang, Jianwu; Hao, Hongtao
Abstract: The objective of this paper is to improve the performance of the synchronizer control strategy by considering the effect of clutch drag torque. The research of synchronization process in wet dual clutch transmission is performed in this paper. The significant effect of clutch drag torque is analyzed by adding a complex clutch drag torque module to synchronizer model. This paper focuses on the development of original estimation method of clutch drag torque. The estimation method offers an effective way to obtain accurate clutch drag torque, and it is applied to develop a new supervisor control strategy. Results have demonstrated that the estimation method has satisfied efficiency and accuracy and the control strategy improves the performance of the synchronizer mechanism significantly. Highlights: We model the synchronization process with independent clutch drag torque model. We analyze the effect of clutch drag torque on ring unblocking and gear indexing. We develop an original online estimation algorithm of clutch drag torque. We design a new supervisor control strategy of synchronizer. Experiment data is introduced to support the validity of model and estimation method.